Monitoring dan Penilaian Tingkat Kesehatan Koperasi pada Dinas Koperasi dan UMKM Provinsi Bali dengan Dukungan GIS - and and (Inform : Jurnal Ilmiah Bidang Teknologi Informasi dan Komunikasi, 2017)
The growth of cooperatives in Indonesia today is very fast, especially the growth of cooperatives in Bali. Based on data from the Department of Cooperatives, Micro, Small and Medium Bali Province the number of cooperatives in bali per June 30, 2016 as many as 4934, this is certainly a positive picture for the growth of cooperatives. The development of micro-credit activities undertaken cooperative is also growing very rapidly, but this is not matched by the quality of the performance of the cooperative itself. These conditions encourage the government oversight of credit unions and savings and loans by issuing a decision on guidelines for the rating of the cooperative based on Regulation Supervision Deputy Ministry of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia Number 01 / Per / Dep.6 / IV / 2016. The process of calculating the cooperative health assessment has now been made but there is still a conventional manner using Microsoft Excel so that experienced problems in the calculation and delivery of information on the results. Supervision of the cooperative in question is difficult because the delay of information and the lack of technology used. Computerized system and geographic information system support can be used to assist in the process of assessment of the level of health and also facilitate cooperative Cooperative Agency in monitoring the cooperative in question.